Optimal DAPT duration: Each in their own time. Issue 1 (1st January 2015) - Hillegass, William B.; Brott, Brigitta C.
Key Points Meta‐analysis of randomized trials shows no significant difference in major adverse cardiovascular events between shorter (3–6 months) and longer (12–24 months) durations of clopidogrel‐based dual antiplatelet therapy (DAPT) after drug eluting stent (DES) implantation. Shorter durations (6 months) of DAPT should be considered in lower risk patients undergoing DES implantation in current practice. Further research should define the optimal agents and duration of DAPT after percutaneous coronary intervention based on patient specific factors.